Transcriptome and targeted hormone metabolome reveal the molecular mechanisms of flower abscission in camellia - Cai, Yanfei; Meng, Jing; Cui, Yinshan; Tian, Min; Shi, Ziming; Wang, Jihua (Frontiers in Plant Science, 2022)
Camellia is among the most ornamentally valuable flowers and plants worldwide. Flower abscission typically causes significant financial losses by the horticultural landscape. Previous research has revealed that phytohormones, transcription factors, and other genes involved in floral development regulate the maintenance and mortality of flowers. In this study, for the first time, the transcriptomes and targeted hormone metabolomics of three developmental stages of the receptacles of two distinct camellia strains (CF: abscission strain, CHF: nonabscission strain) were analysed to determine their roles in regulating blossom abscission in camellia. ABA content was shown to be considerably upregulated throughout all phases of CF development, as were the genes implicated in the ABA production pathway and their downstream counterparts. Highly expressed genes in CF were involved in galactose metabolism, phenylpropanoid biosynthesis, amino and nucleotide sugar metabolism, pentose and glucuronate interconversions, and MAPK. Among others, highly expressed genes in CHF are associated with fructose and mannose metabolism, alpha-linolenic acid metabolism, biosynthesis of secondary metabolites, starch and sucrose metabolism, and cutin, suberin, and wax biosynthesis. A vast variety of stress response-related pathways and redox-related activities were also shown to be active in CHF. In contrast, CF dramatically activated pathways associated with lignin production, keratinogenesis, cell wall biogenesis, and ABA response. A comparative transcriptomic study of the CF and CHF pathways revealed that the downstream response pathways of hormones, including CTK, BR, IAA, ethylene, and GA, were very active in CF, indicating a significant amount of signal transduction and transcriptional regulation by CF. In addition, members of the transcription factor family, such as MYB, bHLH, MADS, and WD40, may regulate flower abscission. A comparative transcriptome analysis of two distinct strains of camellia receptacles elucidates the molecular processes and regulatory characteristics of flower abscission and provides direction for the targeted improvement and breeding of camellia.